2004
DOI: 10.1007/bf03324547
|View full text |Cite
|
Sign up to set email alerts
|

Lower platelet count in healthy centenarians correlates with dispersion of the QT interval

Abstract: We hypothesize that a reduced number of platelets and the maintenance of normal QTd may contribute to extreme longevity and protect centenarians from cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The clinical relevance of the difference in platelet counts between the subjects with and without A-allele should be further established, but even such a minor difference within a reference range of platelet counts has been debatable regarding the etiopathology of diseases such as CVD. 6,11,12 Therefore, the significant association between the FTO gene polymorphisms and platelet counts found in the present study may provide new insights into the areas related to FTO gene research.…”
Section: Discussionsupporting
confidence: 56%
“…The clinical relevance of the difference in platelet counts between the subjects with and without A-allele should be further established, but even such a minor difference within a reference range of platelet counts has been debatable regarding the etiopathology of diseases such as CVD. 6,11,12 Therefore, the significant association between the FTO gene polymorphisms and platelet counts found in the present study may provide new insights into the areas related to FTO gene research.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies did not show any significant change in QTd with age in a healthy older population. In a preceding study, we have demonstrated that centenarians had a QTd value of 49.3 8 23.51 ms, which did not significantly differ from that observed both in younger and older controls [12] . These results lead to the speculation that the preservation of normal QTd values may protect centenarians against cardiovascular events, especially ventricular arrhythmias and sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that controlling for the effect of age and gender, subjective health was not significantly related to any biomarkers, whereas ADL independence was related to a lower level of platelet (r D ¡.26, p D .018) and a higher level of albumin (r D .27, p D .014). Previous studies on centenarians revealed that higher albumin level was related to better functional health (Gondo et al, 2006) and higher levels of hemoglobin and albumin had a significant positive effect on subjective health (Cho et al, 2011), while lower platelet count was related to lower risk of cardiovascular events (Gangemi et al, 2004). Since the current study is interested in the correlates of a multidimensional SA construct, the patterns and pathways were not elaborated through which biomarkers including albumin and platelets manifest themselves in physical and functional health per se.…”
Section: Fundingmentioning
confidence: 93%